A robótica educacional: avanços e desafios para o ensino médio integrado ao técnico - Afecto, Romeu (2024)
This study is associated to the Graduate Program in Education at Nove de Julho University (PPGE-UNINOVE), specifically within the Educational Policies Research Line (LIPED). The object of investigation was the analysis of the process adopted for the implementation of Educational Robotics (ER) in a school offering Integrated High School with Technical Education. The research questions that guided its development were as follows: What approaches were adopted for the implementation of Educational Robotics in a school offering Integrated High School with Technical Education? Does the use of Educational Robotics contribute to the development of skills and competencies in professional and technological training courses, considering the current guidelines for this educational segment? Can Problem-Based Learning (PBL) integrated within a STEAM approach be considered a methodology for implementing Educational Robotics in this context? What advances, difficulties, and challenges are identified for the implementation of Educational Robotics in schools offering Integrated High School with Technical Education? Based on the object and the presented inquiries, the general objective of this study was to analyze the process adopted for the implementation of Educational Robotics (ER) in a school offering Integrated High School with Technical Education. As a methodological approach, this investigation adopted a qualitative approach and was developed through a case study. The universe designated for conducting this research consisted of a State Technical School (ETEC) within the Public Network of the state of São Paulo, which offers courses in the Information Technology field within the scope of Integrated High School with Technical Education. The participants in this study included 3 members of the management team, 17 teachers, and 70 students enrolled in technological courses who used Educational Robotics between 2022 and 2023 in their educational process. Data collection was carried out using the following instruments: documentary survey, questionnaire, semi-structured interview, and focus group. The main results, articulated with the theoretical framework and the documents collected, elucidated the path adopted in the investigated context for the implementation of Educational Robotics in pedagogical practices, highlighting its potential for the teaching and learning process in curricular components of the Information and Communication Technology area, as well as its contributions to the development of skills and competencies and challenges for its integration into the educational process within the scope of Integrated High School with Technical Education.